2021
DOI: 10.52586/4940
|View full text |Cite
|
Sign up to set email alerts
|

New strategies in plastic surgery: autologous adipose-derived mesenchymal stem cells contained in fat grafting improves symptomatic scars

Abstract: No abstract present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies have found that the stromal vascular fraction (SVF) and decellularized extracellular matrices (ECM) may act as enhanced therapeutic medicinal products [ 10 ]. MSCs, biomaterials and platelet-rich plasma are novel regenerative approaches that can be used in chronic skin wounds as well as soft tissue defects [ 11 , 12 ]. More and more investigations confirmed that exosomes (Exos) of MSCs have indispensable roles to regulate angiogenesis-based wound healing [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the stromal vascular fraction (SVF) and decellularized extracellular matrices (ECM) may act as enhanced therapeutic medicinal products [ 10 ]. MSCs, biomaterials and platelet-rich plasma are novel regenerative approaches that can be used in chronic skin wounds as well as soft tissue defects [ 11 , 12 ]. More and more investigations confirmed that exosomes (Exos) of MSCs have indispensable roles to regulate angiogenesis-based wound healing [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that this method is effective for managing scars in a large number of patients. 22 , 23 Previous studies show that the application of SVF can promote tissue healing and maintain the volume of fat transplantation. Li M et al.…”
Section: Introductionmentioning
confidence: 99%
“…Taking adipose tissue-derived MSCs (AD-MSCs) as one of the most accessible and important sources of MSCs, they are currently primarily used in the following areas: (1) Plastic and esthetic surgery: AD-MSCs are widely utilized in plastic and esthetic surgeries. They can be used for tissue filling and repair, such as treating facial wrinkles, skin scars [ 12 14 ], and breast reconstruction [ 15 17 ]. (2) Arthritis and cartilage injury treatment: AD-MSCs have demonstrated potential effects in the treatment of arthritis and cartilage injuries.…”
Section: Introductionmentioning
confidence: 99%